2019
DOI: 10.1002/ijc.32143
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of PARP inhibitors in homologous recombination deficient carcinomas

Abstract: PARP inhibitors (PARPis) have remarkable antitumor activity in BRCA mutant ovarian carcinoma. Emerging evidence has shown that responses to PARPis are not limited to BRCA mutant tumors, but could expand to other homologous recombination deficiency (HRD) carcinomas. However, relatively little is known about the efficacy of PARPis in patients with HRD when compared to non‐HRD carriers. In this systematic review, 13 clinical trials were included and analyzed for the treatment effect of PARPis on progression free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Multiple cancer therapies, such as DNA damage-inflicting irradiation or chemotherapy, are aimed at this vulnerability, however, emerging treatment strategies are aimed to take advantage of disturbed DNA repair systems that may be present in different tumour types. For instance, treatment with PARP inhibitors, which results in increased numbers of doublestrand DNA breaks (DSBs), is clinically effective in carcinomas that are deficient in homologous recombination (HR) 2 , the major error-free pathway that repairs DSBs by predominantly using the sister chromatid as a undamaged template for repair. Careful assessment of the repair capacity of tumour cells can thus influence treatment choice but can also prevent overtreatment, if upfront analysis would predict treatment unresponsiveness.…”
mentioning
confidence: 99%
“…Multiple cancer therapies, such as DNA damage-inflicting irradiation or chemotherapy, are aimed at this vulnerability, however, emerging treatment strategies are aimed to take advantage of disturbed DNA repair systems that may be present in different tumour types. For instance, treatment with PARP inhibitors, which results in increased numbers of doublestrand DNA breaks (DSBs), is clinically effective in carcinomas that are deficient in homologous recombination (HR) 2 , the major error-free pathway that repairs DSBs by predominantly using the sister chromatid as a undamaged template for repair. Careful assessment of the repair capacity of tumour cells can thus influence treatment choice but can also prevent overtreatment, if upfront analysis would predict treatment unresponsiveness.…”
mentioning
confidence: 99%
“…Thus, PARP inhibition, as described by us for CDDP could induce cancer cell apoptosis by ROS‐mediated p53 activation. Consistently with this evidence, as pointed by Yi et al, a phase II clinical trial in gastric cancer showed an increased benefit by PARP inhibitors in patients presenting a functionally compromised ataxia‐telangiectasia mutated protein (ATM) . At this regard, it should be highlighted that ATM not only interferes with DNA repair but also modulates redox stress; in fact, cells lacking wild‐type ATM are prone to ROS accumulation and oxidative stress.…”
Section: Main Mechanisms Of Cancer Cell Death Mediated By the Parp Inmentioning
confidence: 59%
“…As reviewed by Yi et al ., clinical evaluation of PARP inhibitors in different trials and settings highlighted the role of mutations in DNA repair mechanisms as a prerequisite for a significant therapeutic efficacy. However, Yi et al .…”
Section: Main Mechanisms Of Cancer Cell Death Mediated By the Parp Inmentioning
confidence: 99%
See 2 more Smart Citations